pocketbook; foreign speakers; Indonesian language; culture - Ulya Fawaida; Sudarmin Sudarmin; Sigit Saptono; Saiful Ridlo (International Conference on Science, Education, and Technology, 2023)
Study this aim to analyze the ability to think creatively with the use of Microsains KIT on the madrasah program. A draft study this using "Control Group Design". Sample study this is student class VII MTs Raden Umar Said Colo, class VIIB as control, and class VIIA as group experiments that do learning with use comfort KIT on Theory physics in life every day. The variables studied cover Skills to think creatively among students. as an indicator of the ability to think creatively covers Skills of Think fluency, skill thinking flexibility, skill thinking originality, skill elaboration (Elaboration), and Thinking evaluation (evaluation). Measurement ability thinks creative student conducted with To do Pre-test and post-test. Results study prove that learning using the Microsains KIT in a manner significant (p<0.05) can increase smoothness and flexibility in thinking, as well as increase participation participant in activity discussion and practice increase Skills thinking original, Skills detail (elaboration) and Skills Thinking to evaluate (evaluate).